Assessing The Impact of Marine Protected Areas on Food Security of The Bajau Community In Wakatobi National Park, Indonesia - Hidayatullah Hamim (Cerdika: Jurnal Ilmiah Indonesia, 2024)
Global conservation efforts, such as Marine Protected Areas (MPAs), have garnered attention, yet their impact on food security within indigenous sea-nomadic communities remains underexplored. This study examines how MPAs affect the Bajau community in Wakatobi National Park (WNP), Indonesia, focusing on dietary diversity and household food security. The research surveyed 93 households in Mola villages between December 2023 and January 2024. Food security was measured using indicators like the Household Dietary Diversity Score (HDDS) and the Household Food Insecurity Access Scale (HFIAS). Spearman’s correlation and multiple linear regression analyzed relationships between socio-economic variables and food security. Results showed that the Bajau's diet was moderately diverse, with a mean HDDS of 8.04, and food insecurity was relatively low (mean HFIAS = 1.0968). Significant correlations were found between dietary diversity, food insecurity, and dependency ratios. Households with higher education had more diverse diets, while those with higher dependency ratios faced greater food insecurity. Non-fishing households exhibited higher HDDS, likely due to alternative income sources. These findings suggest that while the Bajau community generally experiences moderate food security, vulnerabilities persist, especially in households with higher dependency ratios. Enhancing livelihood diversification and access to education may improve food security and resilience in this sea-nomadic community.